Comparison of Macronutrient and Micronutrient Adequacy Among Pregnant Women in Urban and Rural Areas - Anitasari, Bestfy; Oka, Irmayanti A. (Research and Community Service Unit, Poltekkes Kemenkes Kupang, 2023)
Adequate macronutrients and micronutrients during pregnancy can support optimal fetal growth and development in addition to meeting the needs of the mother to ensure a healthy pregnancy. The region of residence is one of the factors that contribute to determining how nutrition is fulfilled in groups of pregnant women. This study aims to compare the adequacy of macronutrients and micronutrients between pregnant women in urban and rural areas. This study involved 50 pregnant women, 25 in urban areas and 25 in rural areas. Nutritional information was obtained using a food recall questionnaire that was assessed for 3 days, namely on 2 working days (not consecutive) and 1 day off and also using a food frequency questioner (FFQ). Data was analyzed using Chi Square and Results showed a difference in carbohydrate (p=0.049) and protein (p=0.045) consumption between urban and rural pregnant women, while energy (p=0.053) and fat (p=0.056) showed no difference in adequacy. For micronutrients, Vitamin A (p=0.043) and B12 (p=0.042) consumption showed differences between urban and rural pregnant women, while for vitamin C (p=0.065), vitamin B1 (p=0.078), vitamin B2 (p=0.084), B3 (p=0.056), B6 (p=0.075), E (p=0.088), Iron (p=0.052), Folic acid (p=0.067), Calcium (p=0.054), Phosphorus (p=0.055), fiber (p=0.079), showed no difference in consumption between urban and rural pregnant women. The consumption of micronutrients and macronutrients of pregnant women in rural and urban areas showed less intake than recommended. Nutrition education needs to be improved not only focusing on pregnant women but also on adolescent groups, pre-conception period so that early on good consumption patterns have been formed which will always be applied throughout life.